P155 Incidence and significance of vitamin D deficiency at Inflammatory Bowel Disease inception in the COVID era. (21st January 2022) - Rimmer, P; Cheesbrough, J; Palmer, L; Meade, I; Zaman Mim, M T; Mohamed, Z; Shariff, S; Sharma, N; Cooney, R; Quraishi, M N; Iqbal, T
Abstract: Background: Vitamin D, a key regulator of immune response, is known to be lower in Inflammatory Bowel Disease (IBD) patients than the general population. Disparity in the incidence of deficiency between ethnic groups has previously been demonstrated. We measured vitamin D in a unique multi-ethnic inception cohort to correlate this with traditional IBD scores and patient reported outcome measures including the 'IBD Disk'. Methods: Data regarding demographics, ethnicity, faecal calprotectin (FCAL) and baseline blood results including Vitamin D was collected prospectively from January-October 2021, from adults presenting with suspected IBD. Montreal classification, Harvey-Bradshaw Index or Partial Mayo score, endoscopic disease severity indices and IBD Disk score were documented in those with confirmed diagnosis at endoscopy. Vitamin D deficiency was defined as <50nmol/l. Results: 179 patients had a Vitamin D level recorded; 58 Ulcerative colitis (UC), 58 Crohn's disease (CD), 53 non-IBD controls and 10 still awaiting diagnosis. 44(76%) CD, 32(55%) UC and 28(53%) non-IBD control patients were Vitamin D deficient at first presentation. Median levels were lowest in CD, with a significant difference between CD and non-IBD (median 35nmol/l; IQR 24.05 vs. median 48.9nmol/l; IQR 49.1; p=0.004). Regression analysis demonstrated patients with Crohn's disease were four times more likely to have Vitamin D deficiency compared to UC (OR 4.08; 95% CI 1.35–12.36) at diagnosis. No correlation was seen between absolute vitamin D levels or vitamin deficiency state and faecal calprotectin when controlled for various factors regardless of the IBD subtype. The cohort distributions are demonstrated in Figure 1. Within the IBD cohort, Vitamin D levels were significantly lower in Black or Asian patients vs White patients (median 28.5; IQR 20.85 vs median 43.3; IQR 33.95; p=0.004). Figure 2 provides an overview of the cohort distributions. Vitamin D levels at presentation, as demonstrated in Table 1, did not correlate with Disease activity markers (DAMS) whereas baseline haemoglobin did, albeit weakly. Interestingly, Vitamin D and Haemoglobin correlated without reaching statistical significance (Spearman's rho 0.149; p=0.08). Conclusion: Our inception dataset demonstrates high rates of Vitamin D deficiency comparable to prior studies in IBD patients. Both CD and Black or Asian ethnicity were strongly associated with Vitamin D deficiency. Baseline Vitamin D did not correlate with disease activity markers whereas anaemia showed consistent weak association. Our study demonstrates the problem of hypovitaminosis D and the importance of measurement and supplementation, particularly in Black and Asian CD patients, from diagnosis.